Lost christmas [videorecording (DVD)] - Hay, John (Film director); Hyde, Connie; Izzard, Eddie; Mills, Larry; Flemyng, Jason (Inception Media Group, 2014)
On Christmas Eve, ten-year-old Goose hides his fireman father's keys to prevent him from going to work. Instead, his mother drives his dad which has tragic results. A year later, a mysterious stranger arrives to with a special gift which enables a troubled Goose to find what he has lost on Christmas Past.